Anti-Diabetic Potential of Methanolic Leaf Extract of Kigelia africana (Lam.) Benth in Alloxan-Induced Diabetic Rats - Said, S.S. (International Journal of Pharmaceutical & Biological Archive, 2022)
Diabetes mellitus is a metabolic disorder characterized by hyperglycemia and disturbances of carbohydrate, fat, and protein metabolism associated with complete or relative deficiency in insulin secretion or insulin activity. The aim of this research is to investigate the anti-diabetic activities of methanol leaf extract of Kigelia africana on alloxan-induced diabetic rats. The leaf extract was screened for anti-diabetic potential. Twenty rats 3–4 weeks old of mixed sex weighing 60–100 g body weight were divided into five groups (GI-GV), each group containing four rats, Groups GII–GV were induced with diabetes, while GI served as normal control, GII which is the diabetic control is fed with only feed and distilled water, GIII was administered with 5 mg/kg bw of standard anti-diabetic drugs Glibenclamide (GLB), while GIV was orally administered 250 mg/kg bw of leaf extract of K. africana (LEKa) and GV was orally administered 500 mg/kg bw of LEKa. After 14 days of oral administration of extract, the animals were sacrificed and the serum collected for analysis of liver and kidney parameters, lipid profile (total cholesterol, low density lipoprotein cholesterol, high density lipoprotein cholesterol, and triglyceride), hematological parameters (pack cell volume, hemoglobin, white blood cells, lymphocytes, and neutrophils). The LD50 by oral route in rats was >2000 mg/kg body weight. In conclusion, LEKa exhibited anti-diabetic potential in alloxan-induced diabetic rats.